Feasibility Analysis of New History Bookstore Business: Resilience of Retail MSMEs in the Digital Era - Salsabila Sukma; Levi Yani; Muhamad Arif; Puji Afriyeni (Al-Fadilah: Islamic Economics Journal, 2025)
This study aims to analyze the business feasibility of Toko Buku Sejarah Baru, a bookstore that has been operating for nearly 20 years, specializing in the sale of stationery, school supplies, office equipment, textbooks, reading materials, and various types of musical instruments. The analysis is based on five main aspects: legal, market and marketing, financial, management, and human resources (HR). This research employs a qualitative descriptive method using a case study approach through interviews, direct observation, and documentation studies. The results show that Toko Buku Sejarah Baru has fulfilled business legality requirements and is strategically located, giving it a strong competitive advantage. Affordable pricing strategies, a complete range of products, and the use of e-commerce for online sales are key strengths in the marketing aspect. The store also accepts bulk or wholesale orders. Financial records are managed by an administrator using system tools and handled by a senior employee who is a trusted associate of the store manager. A stable management structure and harmonious working relationships further strengthen the HR aspect. Based on these findings, Toko Buku Sejarah Baru is considered a viable business that deserves further development, particularly through digital system improvements and market expansion.